Adaptive coping strategies among credit transfer students: a qualitative study of UPGRIS and DMMMSU partnership program - Dini Rakhmawati; Desi Maulia; Yovitha Yuliejantiningsih (KONSELOR, 2023)
International Credit Transfer was held between Universitas PGRI Semarang and Don Mariano Marcos Memorial University (DMMMSU) Philippines. The students of UPGRIS would learn at DMMMSU for a semester. The language and cultural differences became challenges for the students to adapt to the learning situation. This matter brings psychological challenges for the students. Therefore, they had to promote coping strategies to manage their difficulties. This research determined the adaptive coping strategy of credit transfer students. This qualitative approach research provided the real experience and portrayal of a real research site by directly interacting with the research subjects. The researchers involved four students of the Guidance and Counseling program with credit transfer program status for a semester. The researchers collected the data with a structured interview and documentation. The applied analyses included three matters: data reduction, data presentation, and data verification. The results showed that every participant applied problem-focused coping, plain-problem solving, confrontative strategy, and social support search for instrumental reasons. Universities should provide psychological services to increasing international student’s stress managing skill.